Intra-EU investment protection in a post-Achmea world - George A. Bermann; John P. Gaffney (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2019)
In Commission v Hungary, the CJEU found that Hungary failed to fulfil its obligations under EU law by restricting EU investors' rights. This Perspective considers what the judgment means for the future of intra-EU investment protection, and whether it will approximate the level of protection currently enjoyed under investor-state arbitration.
Keywords: 330